Anxiety management in pediatric cancer patient and their caregiver during hospitalization through music therapy - Cabral-Gallo, María del Consuelo; Delgadillo-Hernández, Alma Olga; Flores-Herrera, Esther Margarita; Sánchez-Zubieta, Fernando Antonio (Psicooncología, 2014)
Objective: Evaluate the efficacy of music therapy for the management of anxiety during the period of hospitalization in pediatric cancer patient and caregiver. Method: Measurement was performed before and after a single music session and compared result of the evaluation of anxiety with control group. 112 patients and 128 caregivers collaborated. The level of anxiety was assessed using Manifest Anxiety Scale (CMAS-R, Reynolds & Richmond, 1997) applied to patients and the Hamilton Scale (HAS; Hamilton, 1959) for caregivers. Statistical analysis was performed using SPSS version 20 program.Results: No significant change was detected in the group of patients in whom the size of the effect is minimal, whereas caregivers provided significant results in 12 of the 13 dimensions of anxiety assessed with a medium effect size.Conclusions: The use of music therapy helps to decrease the anxiety level significantly in caregiver, while the results obtained from the cancer patients did not support the idea of the benefits of releving anxiety.
Keywords: Anxiety; music therapy; childhood cancer; hospitalization.